Theoretical and experimental analysis of negative dielectrophoresis‐induced particle trajectories. Issue 12 (15th May 2022) - Luna, Ramona; Heineck, Daniel P.; Bucher, Elmar; Heiser, Laura; Ibsen, Stuart D.
Abstract: Many biomedical analysis applications require trapping and manipulating single cells and cell clusters within microfluidic devices. Dielectrophoresis (DEP) is a label‐free technique that can achieve flexible cell trapping, without physical barriers, using electric field gradients created in the device by an electrode microarray. Little is known about how fluid flow forces created by the electrodes, such as thermally driven convection and electroosmosis, affect DEP‐based cell capture under high conductance media conditions that simulate physiologically relevant fluids such as blood or plasma. Here, we compare theoretical trajectories of particles under the influence of negative DEP (nDEP) with observed trajectories of real particles in a high conductance buffer. We used 10‐µm diameter polystyrene beads as model cells and tracked their trajectories in the DEP microfluidic chip. The theoretical nDEP trajectories were in close agreement with the observed particle behavior. This agreement indicates that the movement of the particles was highly dominated by the DEP force and that contributions from thermal‐ and electroosmotic‐driven flows were negligible under these experimental conditions. The analysis protocol developed here offers a strategy that can be applied to future studies with different applied voltages, frequencies, conductivities, and polarization properties of the targeted particles and surrounding medium. These findings motivate further DEP device development to manipulate particle trajectories for trapping applications.